Antimicrobial effects of commercial herbs, spices and essential oils in minced pork - Krisch, Judit (Acta Biologica Szegediensis, 2010)
Effect of fresh and dried garlic, onion, thyme and oregano on the bacterial germ count of minced pork stored at 5°C was evaluated. All spices were added in 1% concentration. Furthermore, MIC (Minimal Inhibitory Concentration) values of marjoram and thyme essential oils on Escherichia coli were determined in vitro, and their antibacterial effect was tested in minced pork inoculated with E. coli. In general, fresh spices showed weak or no inhibition on the total cell count of minced pork, or even caused increased microbe count. On the contrary, dried garlic and thyme decreased total cell count with 1 or two orders of magnitude. MIC values for marjoram and thyme essential oils were 0.5 μl/ml and 2 μl/ml, respectively. The essential oils decreased E. coli cell number in minced pork with 1 log cfu after 24 h storage at 5°C.